Molecular response to ultra-intense x-rays studied with ion and electron momentum imaging - Li, Xiang (Kansas State University, 2019)
A new era in ultrafast science has started in the last decade with the advent of x-ray free-electron lasers (XFELs). These machines, which deliver ultra-intense (up to 10²⁰ W/cm²) and ultrashort (down to hundreds of attoseconds) x-ray pulses, have enabled numerous exciting spectroscopic and imaging techniques for exploring structures and dynamics of atoms, molecules, nanomaterials and biological objects. This thesis aims at advancing our understanding of the fundamental interactions between XFEL pulses and molecules by employing experimental techniques based on coincident momentum spectroscopy of the resulting ions and electrons. The work presented here describes the dependence of molecular response on basic x-ray pulse parameters such as wavelength, pulse energy and pulse duration, which is essential for all XFEL applications, and explores the potential of the employed experimental approach for imaging of ultrafast molecular dynamics. More specifically, the dominant x-ray induced processes including sequential photoionization, ultrafast charge rearrangement and molecular fragmentation are studied. And it is observed that because of the charge rearrangement, molecules exposed to ultra-intense x-rays can be ionized more heavily than the isolated atoms with similar photoabsorption cross sections. While the pulse energy mainly determines what interaction products are created (i.e., what is the charge state distribution of the resulting ionic fragments), the pulse duration is found to be the key parameter which determines how fast a particular charge state is reached, and, thus, how large is the kinetic energy of the corresponding ion. With shorter pulses, a certain pair of ionic fragments is created faster and, thus, at a shorter internuclear distance, resulting in more efficient charge rearrangement. This, in turn, results in the enhancement of sequential ionization for shorter pulses. Moreover, signatures of resonance-enhanced x-ray multiple ionization, which were previously reported for atoms, are presented here for molecules. In addition to the fundamental investigations of x-ray – molecule interactions, two imaging schemes for studying molecular dynamics with free-electrons lasers are explored in proof-of-principle experiments. One is the so-called "Coulomb explosion imaging" method. The fragment momentum distribution from iodomethane molecules exploded by XFEL pulses is found to resemble the one expected from the instantaneous explosion of a molecule at equilibrium geometry, potentially providing a robust tool for ultrafast imaging of evolving molecular structures. A time-dependent explosion model is implemented to account for the charge buildup process. The other method is based on ion and electron coincidence measurement, which can fix the ejected electrons with respect to the molecular frame. Combining this method with a sequential two-photon absorption from a single XFEL pulse, a one-pulse pump-probe experiment is carried out on N2 molecules. The transition from the molecular ion N₂²⁺ created by the first absorbed photon to two isolated atomic ions N+ and N+ is observed from the perspective of core-shell electrons, demonstrating the feasibility of time-resolved x-ray electron spectroscopy in the molecular frame.
Keywords: Molecular response; X-ray free-electron laser; Ion and electron momentum imaging